Chaos - Cornwell, Patricia Daniels (New York : William Morrow, an imprint of HarperCollins Publishers, 2016)
On a hot late summer evening in Cambridge, Massachusetts, Dr. Kay Scarpetta and her investigative partner, Pete Marina, respond to a call about a dead bicyclist. It appears that a young woman has been attacked with almost superhuman force.
Keywords: Scarpetta, Kay -- (Fictitious character) -- Fiction; Medical examiners (Law) -- Fiction; Forensic pathologists -- Fiction; Women physicians -- Fiction; Suspense fiction